The effect of protease inhibitors on the cervical mucus of HIV-positive women taking norethindrone contraception. (April 2015) - Atrio, Jessica; Stek, Alice; Vora, Hita; Sanchez-Keeland, Lorraine; Zannat, Ferdous; Natavio, Melissa
Abstract Objective To compare cervical mucus score (CMS) with and without protease inhibitors (PI) before and after taking norethindrone (NET). Study design This two-arm, researcher blinded, non-randomised, prospective study was conducted to evaluate cervical mucus quality in HIV-positive women taking progestin only pills. The study group was taking a PI, and compared to women taking ARV regimens that have demonstrated no significant interaction with NET in prior pharmacokinetic trials with combined oral contraceptives. The women had a cervical mucus score prior to NET administration. Mucus Scoring was repeated after 21 days of steady state exposure to oral NET 0.35 milligrams. Cervical mucus quality was quantified according to the World Health Organisation criteria, which include: volume, consistency, cellularity, spinnbarkeit, and ferning. Results Sixteen women took PI and 17 were controls. Baseline CMS were similar (p ≥ 0.1). After 21 days CMS were similar among the two groups (p = 1). Conclusions HIV-positive women taking PI demonstrated thickened cervical mucus with oral norethindrone 0.35 mg and are similar to HIV-positive women taking no PI therapy. This may suggest no difference in contraceptive efficacy of progestin only pills in HIV-positive women taking PI.